KUALITAS PELAYANAN PEMBUATAN KTP ELEKTRONIK (e-KTP) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN CIAMIS - Beni Hartanto (Journal Of Regional Public Administration (JRPA), 2018)
This study aims to analyze the quality of service in the manufacture of e-ID card implemented by Disdukcapil Kabupaten Ciamis. The theories used are based on relevance to the research problem. The method used in this research is descriptive method through qualitative approach, with the purpose of expressing comprehensively how the services provided in making e-ID card by the Department of Population and Civil Registration of Ciamis Regency. Based on the results of the research shows that the services provided by the Department of Population and Civil Registration in the making of e-ID card has not been optimal, it is seen from the lack of facilities, such as the lack of blank to print KPT own, facility of technology device which often inhibit to the effectiveness of employee , And the convenience of a waiting room for the community as the recipient of the service.